TANGGUNG JAWAB DINAS SOSIAL KOTA PEKANBARU TERHADAP PENYANDANG DISABILITAS TERKAIT KONSEP KESEJAHTERAAN BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 18 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PENYANDANG DISABILITAS - Lili Rahayu; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The implementation of social welfare is aimed at improving the quality of life and social welfare, including for people with disabilities. The duty of local governments to provide welfare for persons with disabilities is stated in the Riau Province Regional Regulation Number 18 of 2013 concerning the Protection and Empowerment of Persons with Disabilities. In it, it explains the rights for persons with disabilities that they should accept and also the obligations of local governments to make it happen by providing protection and empowerment. Based on the background description that has been described above, the authors are interested and raise this issue in the form of a thesis entitled